SHADOW ELECTORAL INFRASTRUCTURE: THE EXISTENCE AND INFLUENCE OF BOTOH - Anggi Fransiska Putri; Supratiwi (SOSIOEDUKASI, 2026)
Indonesian elections are formally democratic yet empirically shaped by informal practices. Among the most persistent undertheorized actors is the botoh. Existing literature treats botoh as transactional vote buyers within clientelism frameworks. This article argues that botoh constitute a shadow electoral infrastructure a durable, patterned informal institutional arrangement that systematically organizes electoral competition. Employing a qualitative synthesis of empirical case studies from multiple Indonesian local elections (Tulungagung, Lamongan, Blitar, Kudus, Banjarnegara, Pamekasan, Rembang, and Central Kalimantan), the analysis reveals that botoh perform three core functions mass mobilization, vote-buying coordination, and propaganda activism through hierarchical, socially embedded networks spanning the entire electoral cycle. Three systemic patterns emerge: standardization of practices across regions, recurrence across election cycles, and candidate dependence on botoh as essential infrastructure. Drawing on informal institutions theory, brokerage, and embeddedness, the concept of shadow electoral infrastructure shifts analysis from actor-level explanations of vote buying to system-level understanding of how elections are organized under weak formal institutionalization. Botoh are not pathologies of democracy but constitutive features of how Indonesian elections actually work.